Socialization of oral health and the potential use of habbatusauda for PKK cadres in Wirogunan Village - Ariyani Faizah; Ganesh Julia Sawitri; Nurul Salsabila; Puji Tri Jayanti; Radetyo Bhumyang Pandu Wirayudha (Universitas Muhammadiyah Magelang, 2024)
PKK is a community-based organization that involves women's participation as cadres. The role of PKK cadres is to be at the forefront of addressing community issues, both general and health-related. Cadres are the spearhead of village community development. They are equipped with various trainings to enable them to disseminate knowledge to the community. The aim of this service activity is to provide education on oral health and the benefits of black seed (habbatussauda) to PKK cadres in Wirogunan, Kartasura, Sukoharjo. The method used is through direct lectures, discussions, consultations, and screenings. The results of this program show an improvement in the cadres' knowledge of oral health.